Formulation of Guava Jelly Incorporated with Moringa Oleifera Leaves Extract as Functional Food - Adnan, Nur Amirah; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2025)
This study explores the development of a functional food product by incorporating Moringa oleifera leaf extract into guava jelly, aiming to enhance its nutritional profile while maintaining desirable physicochemical and sensory properties. Three formulations with increasing concentrations of moringa extract (25%, 35%, and 45%) were prepared alongside a control. Physicochemical analyses revealed significant changes with increasing moringa incorporation: moisture content decreased from 34.66% in control to 29.95% in the highest formulation, while pH varied slightly, maintaining the ideal range for jelly stability. Total soluble solids (TSS) values remained stable across all formulations, averaging 66 °Brix, ensuring sweetness and shelf-life consistency. Texture Profile Analysis (TPA) showed no significant differences in firmness across samples, with values ranging from 5.21 N to 5.59 N. However, the work of shear decreased significantly in higher formulations, indicating a reduction in cohesiveness, with values dropping from 324.80 g·sec in the control to 218.40 g·sec in the highest formulation. Nutritional composition analyses highlighted significant improvements in protein content, with the highest formulation containing 2.02% compared to 1.07% in the control. Carbohydrate levels also increased, peaking at 71.66%, while ash content rose slightly, reflecting the mineral contribution of M. oleifera. A sensory evaluation conducted using a 9-point hedonic scale indicated that while the control was most preferred, formulations with incorporations of moderate M. oleifera leaf extract (F2 with 35%) still retained acceptable taste, texture, and overall appeal. The findings suggest that incorporating M. oleifera leaf extract into guava jelly enhances its nutritional value, particularly in protein and mineral content, while maintaining consumer acceptability. This innovation contributes to advancing functional food development while addressing dietary gaps in nutrient intake.